Inversion of the Riemann-Liouville operator and its dual using wavelets - Baccar, Cyrine; Hamadi, Nadia Ben; Herch, Hajer; Meherzi, Fatma (My University, 2015)
We define and study the generalized continuous wavelet transform associated with the Riemann-Liouville operator that we use to express the new inversion formulas of the Riemann-Liouville operator and its dual.
Opuscula Mathematica
Keywords: inverse problem; Riemann-Liouville operator; Fourier transform; wavelets